Building a Literacy Culture for English Department Student Through Extensive Reading Program - Umar Alfaruq A. Hasyim; Arif Fajar; Yeasy Agustina Sari; Inaad Mutlib Sayer; Nurul Puspita; Suhono, Suhono (Yayasan Payungi Smart Madani, 2022)
xtensive reading has many benefits to increase students' literacy skills and increase their ability to acquire foreign languages. Because in Extensive Reading, students have many choices of material and the type of reading they want. They also have more time compared to intensive reading. In addition, several studies have concluded that extensive reading can improve foreign language acquisition abilities. Therefore, this community service aims at improving students’ English literacy by conducting a program namely extensive reading program. This activity uses the Participatory Action Research (PAR) method, especially focusing on problem solving (problem solving) and participation (participatory). While the strategy used in conducting this program is to mobilize human resources and student potential, in this case the empowerment team is the driving force in building student awareness of the importance of reading. Therefore, the type of activity that will be carried out is Focus Group Discussion. Community service partners in this extensive reading program are students of Tadris English, Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung. At this early stage, this activity is specifically aimed at students who are actively involved in the management of the English Student Association or ESA. Finally, this program was run very well and improve students’ English productive skill and English literacy among the students, and easy searching some source reference at library online.